Realism and Credibility in Mobile Virtual Environments: User Engagement with VR and 360° Video in a Virtual Coffee Shop - Nobaew, Banphot (Journal of Mobile Multimedia, 2025)
This study applied a within-subjects experimental design to examine user engagement, perceived realism, and credibility when experiencing a virtual organic coffee shop through two immersive formats: Virtual Reality (VR) and 360◦ video. The VR system recreated a Hmong hill tribe cafe´ in Chiang Rai, Thailand, while the 360◦ video documented the authentic organic coffee pro- duction process from seed to roast. Forty-one participants experienced both systems in a counterbalanced order. The findings revealed a complex pattern of results: while initial Wilcoxon signed-rank tests found no significant differences between formats when comparing individual matched variables (p > 0.05), comprehensive analysis with Benjamini-Hochberg corrections revealed that VR demonstrated significantly superior presence (Z = −4.10, p < 0.001, r = 0.64), engagement (Z = −4.50, p < 0.001, r = 0.70), and spatial realism (Z = −3.85, p = 0.002, r = 0.60) with large effect sizes. A mixed-effects ordinal regression model confirmed VR’s advantage in purchase intent (β = 0.68, p = 0.011). Crucially, system usability emerged as a critical factor, showing very strong correlations with both overall user experience (ρ = 0.82, p < 0.001) and purchase intent (ρ = 0.70, p < 0.001) regardless of medium. The relationship between perceived authenticity and satisfaction was particularly strong (ρ = 0.55, p < 0.001), while presence (ρ = 0.42, p = 0.006) and credibility (ρ = 0.46, p = 0.003) showed moderate positive associations with purchase intent. These findings demonstrate that while the measurement approach significantly influences detected differ- ences between immersive media, the translation of immersion into consumer behaviour depends on multiple psychological factors, including usability, credibility, and authenticity, rather than the choice of medium alone.